G195 Who's the lead? can a novel tool and targeted simulation training improve paediatric emergency leadership?. (25th October 2020) - Cotton, R; Woodruff, J; Anton, M; Hernandez, P; Lane, M; Narayanan, A; Casanueva, L; Burmester, M
Abstract : Aims: To prospectively measure the impact of the Leadership In Medical Emergencies (LIME) course through objective measurements of self and team perception of leadership and teamwork. Methods: 7 paediatric practitioners attended a one-day LIME course which introduced Crisis Resource Management and a novel LEAD-A-Team tool (table 1 ) followed by 8 simulated emergencies. Modified-Concise Assessment of Leadership Management (CALM) score was prospectively recorded by the leader and an observer. CALM (Nadkarni et al.) was modified to better reflect LEAD-A-Team, resulting in a maximum score of 72. TeamMonitor scores (Stocker et al.) were recorded by team members. Results: In 63% of scenarios, participants gave themselves a higher m-CALM score than the observer. Observer scores did not correlate with seniority. TeamMonitor scores were averaged and converted to percentages. There was an increase of 11% from first to last scenario and a linear relationship between TeamMonitor scores and simulation course time in minutes (Spearman correlation 0.69). We acknowledge that scenario 8 was the participant's second simulation (table 2 ). Conclusions: These results demonstrate differences between self-perceived and observed leadership. There does not appear to be a strong relationship between seniority and perceived leadership. The team's perception of performance improves as the course progresses suggesting the LIME course was impactful.